A novel Z-scheme porous g-C3N4 nanosheet/Ag3PO4 photocatalyst decorated with N-doped CDs for high efficiency removal of antibiotics. Issue 16 (1st April 2020) - Chen, Xiaoyi; Xue, Xiuling; Gong, Xiuwen
Abstract : A novel Z-scheme photocatalyst, PCNNS/AP/NCD, was fabricated via an in situ sedimentation–calcination method with excellent photocatalytic performance in practical applications. Abstract : A number of porous g-C3 N4 nanosheet/Ag3 PO4 /NCDs (PCNNS/AP/NCDs) with little amounts of Ag3 PO4 were synthesized via an in situ sedimentation–calcination method. The PCNNS/AP/NCDs photocatalyst exhibited excellent photocatalytic performance for the photocatalytic degradation of tetracycline (TC) under visible light irradiation at a removal rate of 90.5% in 40 min. The study of the reaction kinetics of the as-prepared samples was in accordance with the pseudo-second-order kinetics, with the correlation coefficient ( R 2 ) being greater than 0.9776. Meanwhile, the photocatalyst was capable of degrading ciprofloxacin (CIP), and showed good performance even under actual water conditions with natural sunlight irradiation, indicating that the photocatalyst has wide practical applications. In addition, the photocatalytic performance and the XRD and FTIR spectra showed no obvious changes even after four photocatalytic degradation cycles, which revealed the high stability of the PCNNS/AP/NCDs photocatalyst. Furthermore, the possible degradation pathways of TC and the possible Z-scheme mechanism were proposed with ˙O2 − and h + as the main active species contributing to photocatalytic degradation. The results provide a novel insight into the fabrication of Z-scheme PCNNS/AP/NCDs and introduce them as an efficient visible-light-responsive photocatalyst for use in practical applications.